Informal City: Paradigma Baru menuju Kota Inklusif dan Berkelanjutan - Syahri Ramadhan; Ratna Patmawati Wisnu Murti; Iwan Kustiwan (Ruang-Space: Jurnal Lingkungan Binaan)
Cities, with their numerous activities and facilities, have inevitably driven urbanization. The World Bank notes that in 2022, 57% of the world's population live in urban areas, which is predicted to continue to increase, especially in developing countries. While urbanization has a positive impact on economic growth, it also brings negative consequences, such as informal settlement. Urban informal settlements are typically located along the riverbanks, railway lines, and on lands without legal rights. They often have limited access to basic infrastructures and services, such as clean water, sanitation, waste management, etc. This research examines the boundaries of formality, the concept of informality, the characteristics of informal cities, and the relationship between informal cities and the New Urban Agenda (NUA). The NUA aims to address urban planning challenges by prioritizing inclusive urban development, including improving the quality of informal settlements to enhance the quality of life in line with the Sustainable Development Goals of 11 (SDGs 11). This study used a qualitative approach by reviewing relevant sources, including articles, books, laws, regulations, and others. Study results highlight the importance of incorporating the interests of informal urban communities into the formal planning process to promote inclusiveness in urban development. Keywords: urbanization; informality; informal city; new urban agenda; inclusive